Collective responses to global challenges: The social psychology of pro-environmental action. (April 2021) - Barth, Markus; Masson, Torsten; Fritsche, Immo; Fielding, Kelly; Smith, Joanne R.
Abstract: The world faces one of its greatest challenges in climate change. As a global challenge, climate change demands a global response. A psychological approach with the goal to motivate large groups to engage in concerted action will need both, a perspective focused on individual factors and a perspective focused on the collective factors. The social identity approach is a promising and underutilized theoretical basis for the latter. In this special issue, we have brought together new and thought-provoking work on the effects of collective-level variables on pro-environmental action that builds on the social identity approach. This editorial will introduce the core idea of the approach and it will argue for its advantages. We will summarize important previous work on some of the essential variables of the approach and we will briefly introduce the contributions to this special issue which will hopefully stimulate more work in the years ahead.